Peran Kepala Kampung dalam Implementasi Kebijakan Dana Kampung Distrik Manimeri - Manuel Horna; Taufani C. Kurniawan; Mafizatun Nurhayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to: 1) To determine the role of the village head in the communication of village fund policy implementation in Manimeri District. 2) To find out the role of the village head in implementing the village fund policy in Manimeri District. 3) To find out the role of the village head in the disposition of village fund policy implementation in Manimeri District. 4) To find out the role of the village head in the bureaucratic structure of implementing village fund policies in Manimeri District. This research was conducted with interviews with the village heads of Banjar Asouy, Atibo and Bumi Saniari. By using descriptive qualitative research methods and using Edward III Analysis and the Miles and Huberman approach model. The role of the village heads of Banjar Ausoy, Atibo and Bumi Saniari is related to communication, that the village head is the power in determining the policy for implementing village funds and conducting socialization to the community. The role of the village heads of Banjar Ausoy, Atibo and Bumi Saniari related to resources, namely the ability of the implementers to implement policies. As for the role of the village heads of Banjar Ausoy, Atibo and Bumi Saniari regarding disposition, it is said that policy implementers have responses or perceptions that strongly support policies, especially in improving development programs. And the role of the village heads of Banjar Ausoy, Atibo and Bumi Saniari related to the bureaucratic structure in carrying out the tasks of implementing village government and implementing village development.